2021
DOI: 10.3390/biom12010030
|View full text |Cite
|
Sign up to set email alerts
|

Gallic Acid Derivatives Propyl Gallate and Epigallocatechin Gallate Reduce rRNA Transcription via Induction of KDM2A Activation

Abstract: We previously reported that lysine-demethylase 2A (KDM2A), a Jumonji-C histone demethylase, is activated by gallic acid to reduce H3K36me2 levels in the rRNA gene promoter and consequently inhibit rRNA transcription and cell proliferation in the breast cancer cell line MCF-7. Gallic acid activates AMP-activated protein kinase (AMPK) and increases reactive oxygen species (ROS) production to activate KDM2A. Esters of gallic acid, propyl gallate (PG) and epigallocatechin gallate (EGCG), and other chemicals, reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…EGCG triggered the demethylase activities of KDM2A and consequently reduced H3K36me2 levels to block rRNA transcription in MCF-7 cells. In this process, the activation of AMPK induced by EGCG is required for KDM2A activation [ 227 ]. Hence, AMPK plays an indispensable role in the EGCG-induced inhibition of tumor proliferation, metastasis, and regulation of the microenvironment and immune responses [ 228 , 229 ].…”
Section: Potential Ampk Modulators Of Natural Products From Herbal Me...mentioning
confidence: 99%
“…EGCG triggered the demethylase activities of KDM2A and consequently reduced H3K36me2 levels to block rRNA transcription in MCF-7 cells. In this process, the activation of AMPK induced by EGCG is required for KDM2A activation [ 227 ]. Hence, AMPK plays an indispensable role in the EGCG-induced inhibition of tumor proliferation, metastasis, and regulation of the microenvironment and immune responses [ 228 , 229 ].…”
Section: Potential Ampk Modulators Of Natural Products From Herbal Me...mentioning
confidence: 99%
“…By modifying the self-assembled nanopreparation, researchers may achieve the desired properties, such as the integrated function of tumour diagnostics and therapy. Gallic acid (GLA) is a polyphenolic chemical component found in plants, such as rhubarb, Eucalyptus macrophylla (Myrtaceae), and Cornus officinalis (Cornaceae) [ 122 , 123 ]. An et al [ 124 , 125 ] demonstrated that GLA-Fe@BSA-PTX NPs exhibit excellent biological safety and can be utilized for both tumour diagnostics and therapy.…”
Section: The Self-assembly Forms Of Csanmentioning
confidence: 99%
“…Kam et al [285] confirmed the mechanism by which gallic acid targets DNA methylation. They showed that this compound reverses DNMT1 at the protein level, causes an accumulation of ubiquitinated protein aggregates and decreases the activities of chymotrypsin-like proteasome, which explains the protective effect of gallic acid on endothelial cell death [285,286].…”
Section: Gallic Acidmentioning
confidence: 99%